Measurement and coordination analysis of land and sea ecological effects of "production-living-ecological" space in Zhejiang coastal zone(基于“三生”空间的浙江省海岸带陆海生态测度与统筹) - 钱玥(QIAN Yue); 乔观民(QIAO Guanmin); 周艺(ZHOU Yi); 马静武(MA Jingwu) (Zhejiang Daxue xuebao. Lixue ban)
Based on the content of the land and sea "production-living-ecological" space, we measure the ecological coordination efficiency of land and sea from 2000 to 2020 by using the land ecological environment quality index, the ocean ecological environment quality index and the coupling coordination model. The results show that: (1) The ecological quality of land and sea "production-living-ecological" space corresponds to the development pattern of territorial space planning. The main production and living space is distributed around the Hangzhou Bay industrial belt and the coastal industrial belt of Wenzhou-Taizhou, where the important ecological space located in the blue security belt in eastern Zhejiang. (2) The comprehensive ecological effects of land and sea have deteriorated, mainly due to the continuously decline of environmental quality during the progress of rapid urbanization. (3) The coupled coordination status of land and sea ecological quality tends to be optimized. Specially, there is a high degree of coordination in Hangzhou Bay, Xiangshan Bay, et al. in northeastern Zhejiang province, where the land and sea joint management is effective. By contrast the land and sea joint management of the bay area in southeastern Zhejiang province needs to be improved. Our study provides the characteristics of the ecological pattern of coastal zone in Zhejiang province, which shows high intensity development in the land as well as quality ecological protection and restoration in the marine space. The results show that the coupling and coordination mode of land and sea bay is land-driven. Therefore, to build a beautiful bay, we need further strengthening the regional ecological governance and the control of functional marine space.(运用生产-生活-生态“三生”空间建立了陆域生态环境质量指数和海域生态环境质量指数，测度了2000—2020年浙江省海岸带湾区生态环境质量演化特征和陆海统筹水平，结果表明：（1）在“三生”空间视角下海岸带生态环境质量格局与国土空间开发具有内在连接性。生产-生活空间对应环杭州湾产业带、温台沿海产业带，生态空间与近海蓝色屏障具有一致性。（2）海岸带生态环境效应恶化，其主要原因是快速城市化导致陆域生态环境质量持续下降。（3）陆海生态环境统筹水平逐步提高。浙东北湾区协调度较高，海陆联动治理取得了一定成效；浙东南湾区海陆联动治理效果不佳。浙江省海岸带生态环境格局表现为，陆域高强度开发，生态环境质量恶化，海域注重生态保护与修复，生态环境质量在一定程度上得到改善。湾区陆海耦合协调模式属于陆域带动型，因此需进一步加强陆域生态环境治理。)